Visitors’ Attendance Trend and Development of Malaysia Agricultural Park, Selangor, Malaysia - Busu, Abdullah Bakri (2007)
Malaysia Agricultural Park Bukit Cahaya Seri Alam, Shah Alam (TPM) has an inconsistent trend of visitor attendance since it was formed (1986) until now (2006). TPM is a qualitative case study location of this research because it is the only unique agro park in Malaysia with agro-forestry concept and also supported by agro-tourism approach. The study uses the qualitative method which involves in-depth interview, document analysis and field observations. In-depth interviews were done with five respondents who had fulfilled certain requirements based on purposive sampling, snowball selection method and maximum variation. The study duration was approximately eight months which began in December 2005 until July 2006. The objectives of the study are firstly to analyze the number of visitors as an indicator for the success of the TPM. The second objective is to do critical analysis on chronological events and the issues affecting the development of TPM. Findings of this research have identified four phases based on the visitors’ attendance. Nevertheless, this is not the real indicator of TPM’s success. The findings show that the “The True Visitor” is the actual indicator for the success of the TPM and it is not based on the regularity of the present visitors’ attendance. The goal of TPM formation is noble. However, its implementation was not well-planned and merely relied on government funding. The research has discovered that there are several factors which influenced the impact of development, function, and image of TPM. The nature of this research will determine the effects of the development and its implication towards the concept practiced by TPM. If this phenomenon at TPM reoccurs, the negative impact on economy would increase and this would contribute to the negative image of this infantile tourism industry in Malaysia. Not only is that energy wasted but also monetary. Furthermore, this research is expected to be fit as a guideline or reference to other associations.